2020
DOI: 10.2147/ccid.s236956
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Assessment of New Topical Cream Containing Two Essential Oils Combined with Tretinoin in the Treatment of Acne</p>

Abstract: Background: Acne is a frequent adolescent disease characterized by inflammatory and noninflammatory lesions whose topical treatment very often presents adverse phenomena such as irritation or resistance to antibiotics that reduce the patient's compliance. The purpose of this study is to compare a commercial product (Acnatac gel) based on clindamycin-tretinoin (CTG) with a galenic compound containing 2 essential oils (Myrtus communisL. and Origanum vulgare) and tretinoin (MOTC) to evaluate its anti-acne effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 19 publications
0
34
0
1
Order By: Relevance
“…Previous clinical studies have demonstrated that plant-derived ingredients or oils remarkably improve inflammatory skin disorders, including acne. 29 , 30 However, whether the ingredients of the skin care products improve the rash in patients with acne through altering the skin microbiota remains unknown until now, which deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous clinical studies have demonstrated that plant-derived ingredients or oils remarkably improve inflammatory skin disorders, including acne. 29 , 30 However, whether the ingredients of the skin care products improve the rash in patients with acne through altering the skin microbiota remains unknown until now, which deserves further investigations.…”
Section: Discussionmentioning
confidence: 99%
“…102,103 Besides, therapies of natural origin should be implemented especially in dermal infections such as a combination of propolis, tea tree oil, and Aloe vera and the combination of Myrtus communisL., Origanum vulgare and tretinoin (MOTC). 104,105 The spontaneous use of broad-spectrum antibiotics in the treatment of MRSA infection must be prohibited, and the ideal treatment should base on the eminent results of the antibiotic sensitivity test. 106,107 New antibiotics are thought to be more effective against MRSA infections such as telavancin and tedizolid.…”
Section: Treatment and Control Of Mrsa Infectionmentioning
confidence: 99%
“…Hence conveniently, added essential oils are able to enhance the dermato-cosmetic properties of the final product, not only by protecting against microbial infections but also contributing to the preservation of the cosmetic formulation [ 15 , 16 ]. Interestingly, they are also used to induce additional benefits to the skin such as anti-acne, anti-aging, skin lightening, and sun protection, among others, in cosmeceutical products, thus rendering them highly valuable to cosmetic industries [ 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%